Psychological study and religious value novel dear, imamku by mellyana - Zahara, Liza; Missriani, Missriani; Fitriani, Yessi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This research is a qualitative one. The problem with this research is what is the psychological aspect of the characters in the novel Dear, Imamku by Mellyana? What are the religious values of the novel Dear, Imamku by Mellyana? The aim of this study is to describe the psychological aspects of religious characters and values in Mellyana's Dear, Imamku, novel. Analysis of the behavior and psychological symptoms of characters uses the psychological theory of personality developed by Sigmun Freud, combining the theory of personality dynamics, defense and conflict mechanisms, and the classification of emotions in the novel. The method used in this study was the method of qualitative content analysis. The data collection technique uses the analysis of document content. The data analysis technique used the technique of summarizing the text in steps; 1) data reduction, 2) data presentation, 3) conclusions. The results of this study show that there are psychological symptoms of characters in Mellyana's Dear, Imamku novel.